2021
DOI: 10.3390/ijms22020906
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Adiponectin Receptor 1 Inhibits Brown and Beige Adipose Tissue Activity in Mice

Abstract: Adult humans and mice possess significant classical brown adipose tissues (BAT) and, upon cold-induction, acquire brown-like adipocytes in certain depots of white adipose tissues (WAT), known as beige adipose tissues or WAT browning/beiging. Activating thermogenic classical BAT or WAT beiging to generate heat limits diet-induced obesity or type-2 diabetes in mice. Adiponectin is a beneficial adipokine resisting diabetes, and causing “healthy obese” by increasing WAT expansion to limit lipotoxicity in other met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, other studies have demonstrated adiponectin as a negative regulatory factor of cold-induced browning/thermogenesis (29)(30)(31)(32). One possible speculation for these conflicted results is that the effect of adiponectin on thermogenesis may be mediated simultaneously through multiple adiponectin receptors or adiponectin signaling (29). Thus, future studies need to clarify these confounding results and the underlying mechanisms of adiponectin in the regulation of energy.…”
Section: Adiponectinmentioning
confidence: 97%
See 1 more Smart Citation
“…However, other studies have demonstrated adiponectin as a negative regulatory factor of cold-induced browning/thermogenesis (29)(30)(31)(32). One possible speculation for these conflicted results is that the effect of adiponectin on thermogenesis may be mediated simultaneously through multiple adiponectin receptors or adiponectin signaling (29). Thus, future studies need to clarify these confounding results and the underlying mechanisms of adiponectin in the regulation of energy.…”
Section: Adiponectinmentioning
confidence: 97%
“…As early as 2015, Hui et al have demonstrated that adiponectin is relevant for coldinduced browning of subcutaneous white adipose tissue via promotion of M2 macrophage proliferation (28). However, other studies have demonstrated adiponectin as a negative regulatory factor of cold-induced browning/thermogenesis (29)(30)(31)(32). One possible speculation for these conflicted results is that the effect of adiponectin on thermogenesis may be mediated simultaneously through multiple adiponectin receptors or adiponectin signaling (29).…”
Section: Adiponectinmentioning
confidence: 99%